Diagnostic Properties and Significance of Tongue in Persian Medicine and Chinese Medicine - Farahi, Omid R.; Mozaffarpur, Seyyed Ali; Gasemi, Vahdi; Wei, Gu; Nazem, Esmaeil; Nejad, Mina Motaleb; Faeghiniya, Mehri; Mojahedi, Morteza (Current Traditional Medicine, 2021)
In the medical schools of old civilizations, the use of clinical findings has been one of the most important diagnostic methods. The features of tongue and pulse have widely been used as important diagnostic factors in Persian medicine and traditional Chinese medicine. These features are like a mirror reflecting the internal states of the body. This study aimed to evaluate the views of Persian and Chinese medical schools on diagnostic indices of the tongue and compare their common points. This review article compiles, categorizes, and analyses the diagnostics indices of the tongue based on Persian medicine and Chinese medicine sources. To benefit from the experiences of other researchers in this field and to search the desired contents, we used online databases, such as Google Scholar, Pubmed, Embase, Scopus, Baidu, and Web of Science. Five relevant indices were assessed: colour, size, shape, movement, coating and taste. In the first four indices, there is a high degree of commonality between the two schools regarding the properties of indices and even how they reason about the inner state of the body and organs, especially coldness-warmness and wetness indices of Mizaj [temperament]. Overall, considering the commonalities between Persian medicine and Chinese medicine in the use of diagnostic indices of the tongue including colour, shape, taste, and move, it is suggested that these commonalities can be used to make a more accurate diagnosis of diseases. It shows that these commonalities have a theoretical basis and have been practiced for a long time; they are worth spreading in the world.
Keywords: persian medicine